Peningkatan Perilaku Hidup Bersih Dan Sehat (Phbs) Melalui Edukasi Kesehatan Pada Masyarakat Di Lingkungan Permukiman Padat Penduduk - Hilal, Achmad; Nurhidayati, Lailiana Garna; Rosdiana, Rosdiana; Rusnita, Rusnita; Anto, Sardi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Clean and Healthy Living Behavior (PHBS) is one of the promotive and preventive efforts in the field of public health. Densely populated areas are vulnerable to various health problems due to density and limited sanitation facilities. This community service aims to improve understanding and practice of PHBS through health education activities. Activity methods include counseling, demonstrations, and mentoring involving the local community. The results of the activities show increased knowledge and positive behavioral changes in aspects of personal hygiene, waste management, and use of clean water. Health education has proven effective as an initial approach in forming a society that is aware of the importance of clean and healthy living.